MANAGING STUDENT MOTIVATION AND LEARNING ACHIEVEMENTS: A CASE STUDY IN FINANCIAL MATHEMATICS CLASS SRIWIJAYA STATE POLYTECHNIC - Rizal Afif AN; Raras Risia Yogasnumurti; Dika Setiagraha (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
Motivation as a part of the learning process is a crucial aspect and some previous research has been showing evidence. Motivation also becomes a part of Emotional Intelligence (EQ) and that is also proven to be involved to improve learning processes and help students understand advance and improve learning achievements. So, students have more enhanced knowledge and skills in competing and facing real work environments. This paper aims to collect data and discover how motivation affects student learning achievement. The hypothesis of this research is that students who have a good learning achievement are students who have a good motivation and also have a positive effect on student learning achievement. The research sample includes 71 students of Sriwijaya State Polytechnic. Motivation and learning achievements were measured by a questionnaire with a lickert scale. Then the data were analyzed through SPSS software. The results show that Motivation has an effect on student learning outcomes.